2016
DOI: 10.1103/physrevb.93.035455
|View full text |Cite
|
Sign up to set email alerts
|

Negative compressibility in graphene-terminated black phosphorus heterostructures

Abstract: Negative compressibility is a many-body effect wherein strong correlations give rise to an enhanced gate capacitance in two-dimensional (2D) electronic systems. We observe capacitance enhancement in a newly emerged 2D layered material, atomically thin black phosphorus (BP). The encapsulation of BP by hexagonal boron nitride sheets with few-layer graphene as a terminal ensures ultraclean heterostructure interfaces, allowing us to observe negative compressibility at low hole carrier concentrations. We explain th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…Very recently, the decrease of the chemical potential with increasing density has been directly observed by ARPES spectroscopy in two-dimensional monolayers of WSe 2 [13] and quasi-three dimensional spin-orbit correlated materials [14], by conductivity measurements in graphene-MoS 2 heterostructures, [15] and by capacitance measurements in graphene-terminated black phosphorous heterostructures. [16] In these experiments the electronic densities are considerably larger than in conventional semiconductor heterostructures, ruling out the spontaneous occurrence of inhomogeneous phases.…”
mentioning
confidence: 90%
“…Very recently, the decrease of the chemical potential with increasing density has been directly observed by ARPES spectroscopy in two-dimensional monolayers of WSe 2 [13] and quasi-three dimensional spin-orbit correlated materials [14], by conductivity measurements in graphene-MoS 2 heterostructures, [15] and by capacitance measurements in graphene-terminated black phosphorous heterostructures. [16] In these experiments the electronic densities are considerably larger than in conventional semiconductor heterostructures, ruling out the spontaneous occurrence of inhomogeneous phases.…”
mentioning
confidence: 90%
“…10), whereas phosphorene 2D electron gas shows exceptional Hall mobility of up to 6000 cm 2 V −1 s −1 and quantum Hall effect in high-quality van der Walls heterostructures. 82 Recent studies have also found that trions and excitons in phosphorene can be tuned by using a transistor topography set-up. 83 It is noted that trions can be used in spintronic-based devices due to their non-zero spin.…”
Section: Applications Of Phosphorene Electronic Devices and Sensorsmentioning
confidence: 99%
“…In high-quality phosphorene-based heterostructures with negative compressibility, a many-body effects strong correlations lead to an enhanced capacitance in 2D electronic systems, suggesting potential for low-power nanoelectronics and optoelectronics. 82 The anisotropy of transport in phosphorene can also be incorporated into devices. FET device performance and speed may be increased by orientating the conducting channel along the AM direction.…”
Section: Applications Of Phosphorene Electronic Devices and Sensorsmentioning
confidence: 99%
“…1 Negative compressibility has been recently observed in atomically thin BP wherein strong correlations results in an enhanced gate capacitance. 18 Importantly, negative compressibility occurs at densities as high as n ≈ 10 12 cm −2 which is achievable in experiment. It was shown that an increase in the gate capacitance of a phosphorene field-effect transistor (FET) originates from such negative compressibility at low electron densities.…”
Section: Introductionmentioning
confidence: 97%
“…17 Encapsulation of few-layer phosphorene by h-BN sheets has resulted in new ultraclean heterostructures which could be ideal anisotropic 2D systems with high mobility and a possible negative com-pressibility of electron/hole gas (κ −1 = n 2 ∂µ/∂n), where n is the density and µ is the chemical potential of the interacting system. 1,[18][19][20] A negative compressibility results from electron-electron interactions, in which the exchange and correlation energies lower the chemical potential as the electron density decreases. This effect has been observed to enhance the capacitance of semiconductor 2D electronic systems by a few percent above the expected geometric capacitance 21 and is experimental evidence for the formation of a charge-density-wave (CDW) phase.…”
Section: Introductionmentioning
confidence: 99%